The anti-diabetic activities of the methanol leaf extract of Phyllanthus amarus in some laboratory animals - Adedapo, Adeolu A; Ofuegbe, Sunday O; Adeyemi, Abiodun A (Asian Journal of Medical Sciences, 2013)
Background: Phyllanthus amarus is used in Nigeria and other parts of the world as a medicinal plant. Aim and objective: The plant is being evaluated for antidiabetic potential because diabetes mellitus has assumed a worldwide dimension and plant with safe potential are being deployed as they are available all year round and are cheap for use by the rural populace. Materials and Methods: The antidiabetic effect of the methanol extract (ME) of Phyllanthus amarus was evaluated in rats. Standard phytochemical methods were used to test for the presence of phytoactive compounds in the plant. Acute toxicity was carried out in mice to determine safe doses for this plant extract. The anti-diabetic activities of the ME of the plant were assessed using some standard tests as well as histological changes in liver, kidney and pancreas. Diabetes mellitus was induced in rats using alloxan while glibenclamide at 0.2mg/kg was the reference drug used in this study. Results: The ME at 200 and 400mg/kg body weight caused a significant reduction of fasting blood glucose, significant change in the oral glucose tolerance test, marked effect in the hypoglycaemic activity test and pronounced reduction on the glucose level of diabetic rats. Histopathologically, there was no visible lesion seen in the liver, kidney and pancreas of extract-treated and glibenclamide-treated groups. Conclusion: This study may have validated the traditional basis for the use of Phyllanthus amarus as an antidiabetic agent. At the doses used, ME also appeared safer than glibenclamide even though the latter is more potent. DOI: http://dx.doi.org/10.3126/ajms.v4i3.6992 Asian Journal of Medical Sciences 4(2013) 23-34